Diterpene Synthase‐Catalyzed Biosynthesis of Distinct Clerodane Stereoisomers. (28th November 2018) - Pelot, Kyle A.; Hagelthorn, David M.; Hong, Young J.; Tantillo, Dean J.; Zerbe, Philipp
Abstract: The diterpene synthase clerodienyl diphosphate synthase 1 (PvCPS1) from the crop plant switchgrass ( Panicum virgatum ) stereoselectively converts ( E, E, E )‐geranylgeranyl diphosphate (GGPP) into the clerodane natural product, cis‐trans ‐clerodienyl diphosphate (CLPP, 1 ). Structure‐guided point mutations of PvCPS1 redirected product stereoselectivity toward the formation of a rare cis ‐clerodane diastereomer, cis‐cis ‐CLPP (2 ). Additionally, an alternative cis ‐clerodane diastereomer, (5 S, 8 S, 9 R, 10 R )‐13 Z ‐CLPP (3 ), was produced when treating PvCPS1 and select variants thereof with the cis ‐prenyl substrate ( Z, Z, Z )‐nerylneryl diphosphate (NNPP). These results support the hypothesis that substrate configuration and minor active‐site alterations impact precatalysis substrate folding in the stereoselective biosynthesis of clerodane diterpenoid scaffolds, and can be employed to provide enzymatic access to a broader range of bioactive clerodane natural products. Abstract : Small change, big difference : Enzymatic and quantum chemical analysis indicate that different substrate configurations and minor active‐site alterations can impact steric control of the switchgrass ( P. virgatum ) class II diterpene synthase clerodienyl diphosphate synthase (PvCPS1), and provide opportunity for the biosynthesis of natural and new‐to‐nature cis ‐clerodane diterpenoid scaffolds.